Implementasi Etika Pemerintahan Dalam Meningkatkan Kinerja Aparatur Pemerintahan Kabupaten Pangandaran - Aep Haris (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This study aims to obtain an answer in research on the implementation of government ethics in improving the performance of government apparatus in Pangandaran Regency. This study uses a qualitative method with a case study approach intended to obtain phenomena in the field so as to produce descriptive data in the form of written words. Techniques in collecting data in this study is to use technical observation, interviews and documentation. The results of this study indicate that the Implementation of Government Ethics in Improving the Performance of the Pangandaran District Government Apparatus is still not effective in its implementation. This is based on the measurement theory put forward by Edward III (in Agustino, 2014: 149-153) stating that, there are four factors or variables that greatly determine the successful implementation of a policy, namely: (1) Communication, (2) Resources, (3 ) Disposition, (4) Bureaucratic Structure. Solving problems that must be done to continue to run indicators of bureaucratic structure at the Regional Secretariat of Pangandaran Regency, while continuing to carry out their duties and functions as they should, because the bureaucratic structure can work, and later there will be an increase in performance carried out by all employees in the Secretariat Pangandaran Regency area.